Development and Statistical Evaluation of Bio-Based Demulsifiers from Mahogany, Neem, and Calabash Oils for Crude Oil Emulsion Breaking - Haruna Ibrahim; Deborah Chidimma Nwakuba; Ibrahim A. Mohammed-Dabo (CV. Science Tech Group, 2026)
The growing demand for environmentally sustainable chemicals in crude oil processing has intensified interest in green demulsifiers as alternatives to conventional petrochemical surfactants, which are often toxic, costly, and poorly biodegradable. This study investigates the synthesis, performance evaluation, and statistical validation of bio-based demulsifiers derived from oils of Khaya spp. (mahogany), Azadirachta indica (neem), and Crescentia cujete (calabash) for crude oil–water separation. The formulations were prepared through controlled thermal blending of lipophilic and hydrophilic components using camphor, paraffin oil, cassava starch, and liquid soap as intermediates and binders. Their efficiencies were evaluated using standardized bottle tests, with a commercial demulsifier from Nigerian National Petroleum Company Limited serving as the reference. The results showed demulsification efficiencies of 96.6%, 93.7%, and 92.6% for the mahogany-, neem-, and calabash-based formulations, respectively, compared with 97.0% for the commercial product. Statistical analysis confirmed significant differences among treatments (ANOVA: F = 69.83, p = 4.44 × 10⁻⁶), while Tukey’s post hoc test revealed no significant difference between the mahogany-based demulsifier and the commercial control (p > 0.05), indicating comparable performance. The mahogany formulation also exhibited the highest reproducibility (SD = 0.20), reflecting stable interfacial activity and consistent separation efficiency. Overall, these findings demonstrate that plant-derived oils are promising renewable feedstocks for eco-friendly demulsifiers, supporting cleaner petroleum-processing practices and circular bioeconomy principles by using biodegradable, sustainable industrial materials. The replacement of persistent petrochemical surfactants with biodegradable bio-based demulsifiers can significantly reduce marine pollution from oil-processing effluents while promoting sustainable resource utilization within a circular bioeconomy framework.